209 NEURO-MEDICAL COMPLICATIONS OF STROKE—TRENDS OVER THE DECADES IN AN ACUTE STROKE UNIT. (18th November 2021) - McGarvey, C; Hobson, H; Greene, S; Cogan, N; McCabe, D; McCarthy, A; Murphy, S; O'Dowd, S; Walsh, R; Coughlan, T; O'Neill, D; Kennelly, S; et al.
Abstract: Background: Neuro-medical complications post-stroke are common and often serious [1]. We first described complications in our stroke cohort in 1998 and sought to assess whether the severity and the nature of neuro-medical complications may have changed over time due to changes in presentation and the processes of care [2]. Methods: Analysis of stroke service database, which captures all neuro-medical complications as part of its portal for the Irish National Audit of Stroke (INAS), was completed. The frequency of each of the 19 complications was expressed as the percentage of patients that developed each complication over a certain year and over 5 years. Historical comparison was made with dataset from 1998, which captured six complications. Results: Data on 1, 283 patients presenting over 5 years between 2015–2019 was collected. The median age of all patients was 71 years (Range 21–101). In all, 19 different post-stroke complications were recorded; 48% (n = 622) had post-stroke pain, while 23.85% (n = 306) had cognitive decline. Data on 100 patients from 1998 was compared for a number of common metrics including; 21.82% (n = 275) of patients developed an LRTI in the 2015–2019 cohort compared with 14%(n = 14) in the 1998 cohort (p = 0.09) while 16.29% (n = 209) of patients developed a swallow disorder compared to 21% (n = 21) in 1998 (p = 0.22). Conclusion: There are high levels of neuro-medical complications in stroke patients. Twenty years has seen extensive investment in hyperacute stroke care yet post-acute care complications did not appear to reduce significantly between this time, albeit with low numbers. Direction of future funding may consider the full spectrum of stroke care.